Writing for the Web : a practical guide - Jeney, Cynthia L. (Upper Saddle River, N.J. : Pearson Prentice Hall, 2007)
Taking a rhetorical approach, Writing for the Web: A Practical Guide discusses how invention, arrangement, and purpose-driven content can make Web writers more authentic and effective. Written for a wide range of audiences, it introduces students to sound Web writing principles and discusses how technologies, interfaces, and data are impacted by the choices the writer makes. Exercises, assignments, and case scenarios encourage students to practice skills such as captioning photos, incorporating links and writing FAQ pages. Realistic projects help readers learn how to organize content, define writing purpose and craft clear messages that will be powerful enough to impact Web site visitors and their behavior. --Publisher description.
1. Introduction to writing for the Web -- 2. Planning and identity -- 3. Developing content -- 4. Common page types -- 5. Style for Web writing -- 6. Important styles for commercial Web sites -- 7. Important styles for informative Web sites -- 8. Entertainment Web sites.
Formerly CIP.
Includes bibliographical references (p. 197-199) and index.
Keywords: Web sites -- Design; Technical writing